1996
DOI: 10.1017/s0950268800001163
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence ofListeriaspecies in prepacked retail sandwiches

Abstract: SUMMARYA survey of 725 prepacked sandwiches was conducted examining for the presence on enrichment, and by plate count, of Listeria species. Sandwiches were found to contain Listeria sp. more frequently than their component foods. Chicken, beef and bacon fillings were associated with more frequent isolation. Salad also was associated with more frequent isolation, but the increase was not significant. On enrichment, over 15 % of sandwiches contained Listeria species. L. innocua and L. monocytogenes were the onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Other than well-known restaurants and restaurants chains, consumers can find many alternatives, such as ready to eat (RTE) sandwiches and takeaways, in order to eat out. However, such prepared foods are considered to be susceptible to post-preparation contamination by pathogenic bacteria (37). The country's economic circumstances, social difficulties, life styles and presence of urban characteristics, among other factors, contribute to the growth of the informal sector of the economy, including street food vending.…”
Section: Introductionmentioning
confidence: 99%
“…Other than well-known restaurants and restaurants chains, consumers can find many alternatives, such as ready to eat (RTE) sandwiches and takeaways, in order to eat out. However, such prepared foods are considered to be susceptible to post-preparation contamination by pathogenic bacteria (37). The country's economic circumstances, social difficulties, life styles and presence of urban characteristics, among other factors, contribute to the growth of the informal sector of the economy, including street food vending.…”
Section: Introductionmentioning
confidence: 99%
“…Examination of refrigerated RTE sandwich products available for purchase from either retail stores or vending machines indicates they have relatively short shelf-lives that range from as little as 24 to 96 h. Because RTE sandwiches are multi-ingredient products that require assembly by humans, they are especially susceptible to post-process contamination by pathogenic bacteria (Wilson, 1996). Such products, which require little of no preheating before consumption, are therefore a potential reservoir for foodborne pathogens and a source of foodborne illness.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work (16) has indicated that a radiation dose of 1.5 kGy represses the postirradiation growth of L. monocytogenes inoculated onto RTE meats for 1 to 2 weeks and that postirradiation growth of the microorganism is completely inhibited when additives such as sodium diacetate and potassium lactate mixtures are included in RTE meat-product formulations (16). Given the short shelf life of such products, Յ1 week, and based on the data obtained in L. monocytogenes detection studies (5,10,23), a radiation dose of 2.0 kGy would eliminate the bacterium from 99.9% of RTE products and be unable to proliferate in the remainder. If additional protection were required, use of deli meats that contain additives such as sodium diacetate and potassium lactate mixtures for inclusion in the assembled RTE wrap products would ensure a minimum 3-log reduction without the possibility of L. monocytogenes regrowth in tortilla wrap-type products regardless of shelf life.…”
Section: Resultsmentioning
confidence: 99%
“…While the vast majority of luncheon meats and bagged salad vegetables contaminated with L. monocytogenes contain relatively low levels (Յ10 2 CFU/g) of the microorganism, it is not unusual that products subjected to temperature abuse (10ЊC) may contain Ն10 4 CFU/g of L. monocytogenes (10,13,23). Wilson (23) found that 15% of prepacked retail sandwiches contained Listeria spp.…”
Section: Resultsmentioning
confidence: 99%